Single coronary ostium in a patient with quadricuspid aortic valve combined with aneurysmal ascending aortic dilatation - Do Yeon Kim (Journal of Cardiothoracic Surgery, 2017)
Abstract Background The presence of a fourth aortic valve cusp (quadricupsid aortic valve) is a rare congenital malformation and is often accompanied by other anomalies of the adjacent cardiovascular structures. Among these concomitant anomalies, simultaneous association of both a single coronary ostium and aneurysmal ascending aortic dilation in combination with the quadricupsid aortic valve has not been reported yet. Case presentation We experienced the case of a 56-year-old female patient presenting as aortic regurgitation resulted from malcoaptation of quadricupsid aortic valve. The patient had also accompanying aneurysmal ascending aortic dilatation and coronary ostial anomaly. Surgical correction (aortic valve replacement with mechanical devices and supracoronary aortic replacement with prosthetic graft) was performed without any complications. Conclusions The technological development of preoperative imaging studies enable the physician to encounter the quadricuspid aortic valve with other associated malformations more often unlike previous reports. With review on the quadricuspid aortic valve, we discussed a surgical considerations for the treatment of this anomaly.